LOFER CYCLOTHEMS FROM THE LOWER KRKA LIMESTONES (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1993)
The complete Lofer cyclothems were for the first time found in the Lower Liassic from the Slovenia part of Outer Dinarides. The Lower Liassic sequence at Krka composed of shallow water lagoonal limestones was formed in subtidal, intertidal and supratidal environment. The sequence is characterized by predominantly dark gray carbonate sediments among which micritic, biomicritic, oomicritic and oncomicritic Iimestones prevail. The main characteristic of Krka limestones is the well-developed rhythmic sedimentation. The cycles are composed of three members, such as cyclothems in the type-locality Loferer Steinberge.
Keywords: Cyclothems; Jurassic; Lower Liassic; Sedimentology; Outer Dinarides; Southern Slovenia.